Rapid systemic surge of IL-33 after severe human trauma: a prospective observational study - Olav Sundnes; William Ottestad; Camilla Schjalm; Peter Lundbäck; Lars la Cour Poulsen; Tom Eirik Mollnes; Guttorm Haraldsen; Torsten Eken (BMC, 2021)
Abstract Background Alarmins are considered proximal mediators of the immune response after tissue injury. Understanding their biology could pave the way for development of new therapeutic targets and biomarkers in human disease, including multiple trauma. In this study we explored high-resolution concentration kinetics of the alarmin interleukin-33 (IL-33) early after human trauma. Methods Plasma samples were serially collected from 136 trauma patients immediately after hospital admission, 2, 4, 6, and 8 h thereafter, and every morning in the ICU. Levels of IL-33 and its decoy receptor sST2 were measured by immunoassays. Results We observed a rapid and transient surge of IL-33 in a subset of critically injured patients. These patients had more widespread tissue injuries and a greater degree of early coagulopathy. IL-33 half-life (t1/2) was 1.4 h (95% CI 1.2-1.6). sST2 displayed a distinctly different pattern with low initial levels but massive increase at later time points. Conclusions We describe for the first time early high-resolution IL-33 concentration kinetics in individual patients after trauma and correlate systemic IL-33 release to clinical data. These findings provide insight into a potentially important axis of danger signaling in humans.